Phosphorylation of conserved casein kinase sites regulates cAMP-response element-binding protein DNA binding in Drosophila. - Horiuchi, J.; Jiang, W.; Zhou, H.; Wu, P.; Yin, J.C. (Journal of Biological Chemistry, 2004)
The Drosophila homolog of cAMP-response element-binding protein (CREB), dCREB2, exists with serine 231, equivalent to mammalian serine 133, in a predominantly phosphorylated state. Thus, unlike the mammalian protein, the primary regulation of dCREB2 may occur at a different step from serine 231 phosphorylation. Although bacterially expressed dCREB2 bound cAMP-response element sites, protein from Drosophila extracts was unable to do so unless treated with phosphatase. Phosphorylation of recombinant protein by casein kinase (CK) I or II, but not calcium-calmodulin kinase II or protein kinase A, inhibited DNA binding. Up to four conserved CK sites likely to be phosphorylated in vivo were responsible for this effect, and these sites were phosphorylated by a kinase present in Drosophila cell extracts that biochemically resembles CKII. We propose that the relative importance of different signaling pathways in regulating CREB activity may differ between Drosophila and mammals. In Drosophila, the dephosphorylation of CK sites appears to be the major regulatory step, while phosphorylation of serine 231 is necessary but secondary.